Blackleg of Potato - Sparks, Adam; Kennelly, Megan M. (My University, 2008)
Black leg of potato, caused by the bacterium Erwinia carotovora subsp. atroseptica, is a common potato disease in Kansas. This is a guide to controlling the bacterium.
EP149_2008-08
Keywords: EP149; Crops; Lawn and Garden; Health and Safety; EP